School turnaround in North Carolina: A regression discontinuity analysis. (February 2018) - Heissel, Jennifer A.; Ladd, Helen F.
Highlights: Paper examines school turnaround in North Carolina elementary and middle schools. Turnaround efforts did not improve and may have decreased math and reading scores. Program increased administrative burdens. Abstract: This paper examines the effect of a federally supported school turnaround program in North Carolina elementary and middle schools. Using a regression discontinuity design, we find that the turnaround program did not improve, and may have reduced, average school-level passing rates in math and reading. One potential contributor to that finding appears to be that the program increased the concentration of low-income students in treated schools. Based on teacher survey data, we find that, as was intended, treated schools brought in new principals and increased the time teachers devoted to professional development. At the same time, the program increased administrative burdens and distracted teachers, potentially reducing time available for instruction, and increased teacher turnover after the first full year of implementation. Overall, we find little evidence of success for North Carolina's efforts to turn around low-performing schools under its Race to the Top grant.